2018
DOI: 10.1093/jas/sky390
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of longevity for improving profitability of beef cattle1

Abstract: The objective of this study was to estimate genetic parameters for longevity and assess the suitability of using these selection criteria to improve the genetic merit of the beef cattle population of the Czech Republic. The performance record database, which contains records of 363,000 beef cattle animals of 19 breeds and their crosses, was used. The populations of Charolais and Aberdeen Angus were large enough that the genetic parameter estimations and all analyses were done for these breeds separately. Two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…In general, most peaks of heritability observed for the different longevity definitions analyzed in our study occurred between 4 to 7 years, which indicates that performing selection within this interval can help to accelerate the genetic gain for longevity. This is in agreement with Brzáková et al [ 11 ], who reported that the highest heritabilities were estimated at 6.5 years. On the other hand, the highest heritability reported by Jamrozik et al [ 13 ] was estimated at 2 years.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In general, most peaks of heritability observed for the different longevity definitions analyzed in our study occurred between 4 to 7 years, which indicates that performing selection within this interval can help to accelerate the genetic gain for longevity. This is in agreement with Brzáková et al [ 11 ], who reported that the highest heritabilities were estimated at 6.5 years. On the other hand, the highest heritability reported by Jamrozik et al [ 13 ] was estimated at 2 years.…”
Section: Discussionsupporting
confidence: 93%
“…Heritabilities. Genetic analysis of longevity (or longevity-related traits, such as stayability and survival) are becoming popular in livestock breeding research [ 11 , 13 , 53 ]. However, to our best knowledge, there are no studies evaluating the impact of different culling reasons in the estimation of variance components and genetic parameters for longevity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations